Flexural Behavior of Composite GFRP Pultruded I-Section Beams under Static and Impact Loading - Abbas A. Allawi; Safaa I. Ali (Civil Engineering Journal, 2020)
In this study, the effect of glass fiber reinforced polymer (GFRP) section and compressive strength of concrete in composite beams under static and low velocity impact loads was examined. Modeling was performed and the obtained results were compared with the test results and their compatibility was evaluated.‎ Experimental tests of four composite beams were carried out, where two of them are control specimen with 20 MPa compressive strength of concrete deck slab and 50 MPa for other. Bending characteristics were affected by the strength of concrete under impact loading case, as it increased maximum impact force and damping time at a ratio of 59% and reduced the damping ratio by 47% compared to the reference hybrid beam. Under static loading, there was an increase in all the parameters, including the maximum load, ductility, and stiffness. Mid-span deflection was reduced by 25% under static and impact loads. A finite element analysis was performed by using the ABAQUS software. The midspan deflection value was greater than the experimental values by 6% and 3% for impact and static loads, respectively, and all other results showed a high rate of agreement with the obtained test results. The agreement between the numerical and experimental results indicates that the developed numerical model is capable of analyzing the impact and static behavior of such hybrid GFRP-concrete system. Doi: 10.28991/cej-2020-03091608 Full Text: PDF